2019
DOI: 10.1002/jcb.28935
|View full text |Cite
|
Sign up to set email alerts
|

The effect of miR‐579 on the PI3K/AKT pathway in human glioblastoma PTEN mutant cell lines

Abstract: Glioblastoma multiform (GBM) is a type of aggressive brain cancer with limited success in standard treatment. MicroRNAs are one of the most beneficial tools for diagnosis, prognosis, and treatment of cancer. This study aimed to investigate the effect of miR‐579 on cellular behaviors and expression of PI3K/AKT signaling pathway in GBM cell lines. In the present study, miR‐579 was overexpressed in U251 and A‐172 cell lines by using lentil vector, and its effect on cellular behavior such as proliferation and migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Furthermore, the observed reversion of the core miRNA expression levels on differentiation, and, therefore, the loss of stemness properties ( Figure 2B), further support that the five core miRNAs identified are regulators of CSC stemness properties. Except for miR-224, the other four miRNAs have previously been reported to be tumor suppressors [65][66][67][68]. Hence, circRNA knockdown of these tumor suppressor miRNAs shown here ( Figure 5B) is consistent with involvement of circ_0066631 and circ_0082096 in the tumorigenesis process.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the observed reversion of the core miRNA expression levels on differentiation, and, therefore, the loss of stemness properties ( Figure 2B), further support that the five core miRNAs identified are regulators of CSC stemness properties. Except for miR-224, the other four miRNAs have previously been reported to be tumor suppressors [65][66][67][68]. Hence, circRNA knockdown of these tumor suppressor miRNAs shown here ( Figure 5B) is consistent with involvement of circ_0066631 and circ_0082096 in the tumorigenesis process.…”
Section: Discussionsupporting
confidence: 84%
“…miR-579 was obviously associated with overall survival and tumor-specific survival of patients with locally advanced rectal cancer [32]. Upregulation of miR-579 could block proliferation, cell cycle, migration and also trigger the apoptosis of glioblastoma multiform cells [24]. Our study demonstrated that miR-579 was downregulated in OS cells, and transfection with miR-579 mimic inhibited the proliferative, invasion, and EMT capabilities of OS cells, which could be reversed by lncRNA NEAT1 overexpression.…”
Section: Discussionmentioning
confidence: 61%
“…Importantly, emerging evidence has pointed out that miRNAs participate in OS, such as miR-18a-5p, miR-671-5p, miR-1301, and miR-212 [19-22]. MiR-579 was reported to be associated with malignancies, such as breast cancer, ovarian cancer, and human glioblastoma [23][24][25]. However, its function in OS deserves further studies.LncRNAs are proved to serve as competing endogenous RNAs (ceRNAs), which sponges certain miRNAs to mediate its target gene, thus changing the post-transcriptional regulation [1].…”
mentioning
confidence: 99%
“…After 72 h of transduction total RNA was isolated from U251 and A-172 cell lines using the TRIzol reagent (Invitrogen, Carlsbad, CA) according to the company instructions. Complementary DNAs (cDNAs) were manufactured with M-MuLV Reverse Transcription enzyme (Thermo Fisher Scientific, USA) with stem-loop RT primers (for miRNAs and SNORD47) and random hexamers (for genes) 17 . The Real Time-PCR reactions were done using the RealQ Plus 2x Master Mix Green (Ampliqon, Odense M, Denmark) according to the company instructions.…”
Section: Gene Expression Analysismentioning
confidence: 99%